Print Advertising Copy Testing: - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
, ABSTRACTS This article alms 0 develop an integral overview of the present status of the theory of the copy testing vaiidity. It includes the presentation of the theoritical consideration or conceptual Issues in copy testing, some empirical results or findlrig in copy testing, and finally, proposes an alternative conceptual framework of copy testing that a company can Use to Improve. validity in copy testing especially In print copy testing.